The Conflict Between Reason And Emotion In Daniel Keyes’ Novel "Flowers For Algernon" - Ziyaeva, Shirin (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
In world literature, works aimed at artistic analysis of the human psyche and thought processes occupy a special place. In 20th-century American literature, Daniel Keyes’ novel "Flowers for Algernon" is one of such works. The author raises the most important questions of humanity through the artificially acquired intelligence of a simple worker, Charlie Gordon. The work reveals the imbalances that arise in the world of emotions, the pursuit of happiness and its tragic end, along with the expansion of human consciousness, based on deep psychological analysis.